The posters of May ’68 and their significance for a contemporary critique of capitalism - Irwin, Jones (Estudios de Filosofía, 2020)
This essay explores the original political significance of the posters of May ’68 as a critique of capitalism, as well as extending this approach to a critique of contemporary capitalism in 2020. The slogans of ’68 are deceptively simple and we look to the importance of the political ideas expressed aesthetically as having immediate impact in the late 1960s, but also the underlying Situationist philosophy which influenced them. We also explore the contemporary significance of Situationist theory, especially in the context of the renewal of Marxist thought in the 21st century. This renewed Leftist critique of capitalism emerges as articulated through newer social and political movements of the current times, particularly through the political philosophy of Slavoj Žižek and his auto-critique of the former Yugoslavia.